ЭРКИН АЪЗАМ КИНОҚИССАЛАРИ ТИЛИНИНГ ПРАГМАТИК ХУСУСИЯТЛАРИ - Холмуродова, М.И. (SCIENCE and SOCIETY, 2020)
The article describes the pragmatic, socio-pragmatic features of the language of cinema-tales by Erkin Azam, the pragmatic interpretation of communication between the addresser and the addressee. The process of socio-pragmatic specialization of speech is also observed in films.
Keywords: pragmatics; sociopragmatic; addressee; addresser; speaker; listener; text; author; pragmatic task; pragmatic meaning